DUKUNGAN DAN IMPLEMENTASI SOUTH-SOUTH COOPERATION INDONESIA DALAM MENINGKATKAN PERTUMBUHAN NEGARA BERKEMBANG - Fahrul Rozy (UIR Press, 2020)
South South Cooperation (SSC) is a form of development cooperation between developing countries based on the principle of equality, solidarity, and the principle of mutual benefit. Indonesia is one of the member countries of Cooperation which is active as a foreign aid provider for SSC partner countries. Indonesia started the Cooperation since the Asian African Conference 1955 in Bandung.. Nevertheless, there are still many problems in implementing this policy. Not every Indonesian understand about this issue or the need of giving aid to other developing countries while there are still many development problems occurring in our domestic level. This study is aimed to analyze the importance of why Indonesia giving overseas development aid through SSC scheme. Besides that this article is aimed to identify the challange of Indonesia in implementing SSC and examines from another perspective on the impact of Indonesia's foreign assistance on the development of member states of SSC. This paper adopting a qualitative method of analysis. Its finding concludes that the country’s involvement is intended to gain political support from developing countries for the country’s political interest in international arena and it has given significant contribution for the country’s economic development, especially in the regions